Pharmacological Intervention in Hepatic Stellate Cell Activation and Hepatic Fibrosis - Schon, Hans-Theo; Bartneck, Matthias; Borkham-Kamphorst, Erawan; Nattermann, Jacob; Lammers, Twan; Tacke, Frank; Weiskirchen, Ralf (Frontiers in Pharmacology, 2016)
The activation and transdifferentiation of hepatic stellate cells (HSCs) into contractile, matrix-producing myofibroblasts (MFBs) are central events in hepatic fibrogenesis. These processes are driven by autocrine- and paracrine-acting soluble factors (i.e. cytokines and chemokines). Proof-of-concept studies of the last decades have shown that both the deactivation and removal of hepatic MFBs as well as antagonizing profibrogenic factors are in principle suitable to attenuate ongoing hepatic fibrosis. Although several drugs show potent antifibrotic activities in experimental models of hepatic fibrosis, there is presently no effective pharmaceutical intervention specifically approved for the treatment of liver fibrosis. Pharmaceutical interventions are generally hampered by insufficient supply of drugs to the diseased liver tissue and/or by adverse effects as a result of affecting non-target cells. Therefore, targeted delivery systems that bind specifically to receptors solely expressed on activated HSCs or transdifferentiated MFBs and delivery systems that can improve drug distribution to the liver in general are urgently needed. In this review, we summarize current strategies for targeted delivery of drugs to the liver and in particular to pro-fibrogenic liver cells. The applicability and efficacy of sequestering molecules, selective protein carriers, lipid-based drug vehicles, viral vectors, transcriptional targeting approaches, therapeutic liver- and HSC-specific nanoparticles, and miRNA-based strategies are discussed. Some of these delivery systems that had already been successfully tested in experimental animal models of ongoing hepatic fibrogenesis are expected to translate into clinical useful therapeutics specifically targeting HSCs.